Assessing diverse swards and regenerative management for mitigating nitrous oxide emissions from urine patches : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Animal Science at Massey University, Manawatū, New Zealand. EMBARGOED until 31st March 2027 - Qiao, Xiaonan (Massey University, 2025)
Nitrous oxide (N₂O) is a potent greenhouse gas and is a significant driver of climate change. Grazing systems are geographically extensive and a major contributor to rising N₂O levels, due to their reliance on synthetic nitrogen (N) fertilisers to meet production goals. Increasing regulation and public scrutiny are currently driving a re-evaluation of N use in agricultural systems. The adoption of regenerative farming practices for livestock production, represents a potential management strategy for the reduction of N₂O emissions from grazing systems. Regenerative grazing systems are typically characterised by reduced N inputs, use of diverse pastures (i.e., grasses, legumes, and herbs), longer grazing rotations, and higher post-grazing residuals, which are expected to impact plant growth and soil function/health, potentially increase N use efficiency and biodiversity, and thus affect N₂O emissions. This study site was located at Massey University's Dairy No.1 Farm in Palmerston North, New Zealand (40°22'35"S, 175°36'49"E). Three adjacent paddocks were selected at this site, with similar soil type, classified as sandy loam soil. A total of 60 static chambers were used to measure N₂O emissions from 3 different pastures: i) perennial ryegrass (Lolium perenne L.) and white clover (Trifolium repens L.) under contemporary management (Std-Con); ii) hyper-diverse pasture under regenerative management (Div-Reg); and iii) hyper-diverse pasture under contemporary management (Div-Con). Three months before the study commenced, grazing cows (Jerseys, Friesians and Crossbreds) were excluded from accessing the pastures. Static flux chambers (250 mm diameter × 200 mm height) were inserted 100 mm into the soil 2 weeks prior to the initial sampling. Soil samples (~10 cm) were taken adjacent to the chambers to assess nutrient content. Each pasture system had 24 dairy cows which only grazed that system. On day 0, fresh urine was collected opportunistically from each group of cows and was uniformly applied inside half of the chambers within each respective pasture at a rate of 10 L/m². Day 0 N₂O flux measurements were collected 4 hours after urine application, with measurement repeated at 1, 2, 3, 6, 10, 13, 16, 20, 23, 28, 30, 38, 44, 55, 56, and 70 days. Data were analysed as repeated measurements and the area under the curve was computed by trapezoidal rule representing the cumulative emissions. The N concentration of applied urine was 0.3% in the Std-Con and Div-Reg, and 0.2% in the Div-Con. Nitrous oxide emissions in urine patch from the Std-Con and Div-Con pastures were both significantly (P<0.01) greater (55%), compared to Div-Reg pasture system. When urine was applied, cumulative N₂O emissions throughout the study period were 3.57, 3.44, and 1.56 kg N₂O-N/ha for Div-Con, Std-Con, and Div-Reg, respectively. These findings suggest a potential role for regenerative practices to mitigate N₂O emissions.
Embargoed until 31st March 2027
Keywords: 300307 Environmental studies in animal production